Symptoms of anal incontinence and quality of life: a psychometric study of the Norwegian version of the ICIQ-B amongst hospital outpatients - Susan Saga; Anne Guttormsen Vinsnes; Christine Norton; Gørill Haugan (BMC, 2022)
Abstract Background The International Consultation on Incontinence Questionnaire-Bowel (ICIQ-B), a self-report, condition-specific questionnaire designed to assess symptoms of anal incontinence (AI), measures AI's impact on quality of life (QoL) along with perceived bowel patterns and bowel control amongst individuals with AI. In our study, we aimed to translate the ICIQ-B to Norwegian and investigate the Norwegian version's psychometric properties. Methods To establish a relevant, comprehensive, and understandable Norwegian ICIQ-B, cognitive interviews were conducted with 10 patients with AI, and six clinical experts reviewed the translated scale. The Norwegian ICIQ-B's structural validity, scale reliability, and content validity were tested amongst patients with AI attending hospital outpatient clinics in three regions of Norway (N = 208). Results Assessing the Norwegian ICIQ-B's content validity revealed that the questionnaire was relevant, comprehensive, and understandable. Missing data were infrequent (3.3%), and no floor or ceiling effects emerged. Three-factor and two-factor solution models, both with advantages and disadvantages, were found. The three-factor model offered the most parsimonious solution by covering most of the original scale, albeit with an unacceptably low reliability (α = .37) for the construct of bowel pattern. The two-factor model showed good reliability in terms of internal consistency for the constructs of bowel control (α = .80) and impact on QoL (α = .85) but was less parsimonious due to dismissing seven of the original 17 items and excluding the bowel pattern construct. Test-retest reliability demonstrates good stability for the Norwegian version, with an intra-class correlation coefficient of .90-.95 and weighted kappa of .39-.87 for single items. Conclusions Although the Norwegian version of ICIQ-B demonstrates good stability and content validity, the original constructs of bowel pattern and bowel control had to be adapted, whereas the construct of impact on QoL remained unchanged. Further psychometric testing of the Norwegian ICIQ-B's factor structure is therefore recommended.